3D technology to measure dental arches and create a template for lingual brackets technique - KAIRALLA, Silvana Allegrini; CAPPELLETTE JR, Mario; VELASCO, Leandro; FERREIRA, Leila Soares; PIGNATARI, Shirley Shizue Nagata (Dental press journal of orthodontics, 2021)
ABSTRACT Objective: This study aims at identifying anatomical dimensions of dental arches, based on landmarks currently used in the lingual orthodontic technique, and create an archwire form template to be used in orthodontic clinics. Methods: Maxillary and mandibular dental casts of 140 Caucasian individuals with natural and normal occlusion were digitized (3D), and the images were analyzed with Delcam Power ShapeTM 2010 software. The dental arch shapes and sizes were obtained from 14 landmarks selected on the lingual surface of the teeth. Points and segments defined by the software were used to create an archwire form template. Results: Various dental arch patterns were found for both maxilla and mandible. The smallest sizes were found in females, and the largest were found in male subjects. Six categories were defined for each gender, three for the maxilla and three for the mandible (Small, Medium and Large). A template was created with eighteen anatomic lingual archwire designs, nine for the maxilla and nine for the mandible, for both genders. Conclusions: Landmarks evaluated in this study showed dental arch differences between genders. This information enables making orthodontic lingual archwires that are more compatible with the anatomical forms and sizes of the maxilla and mandible. The findings also allowed the creation of a template for an anatomic lingual metallic archwire form to be used in the lingual technique. RESUMO Objetivo: O presente estudo tem como objetivo encontrar as formas anatômicas e dimensões das arcadas dentárias com base em pontos de referência utilizados na técnica ortodôntica lingual, e criar um diagrama com um maior número de arcos metálicos para serem utilizados na clínica ortodôntica. Métodos: 140 modelos de indivíduos caucasianos com oclusão normal e natural foram digitalizados (3D) e as imagens, analisadas com o software Delcam Power ShapeTM 2010. A determinação das formas e tamanhos das arcadas dentárias foi obtida a partir de 14 pontos selecionados na superfície lingual dos dentes. Outros pontos e segmentos foram utilizados, com o auxílio do software, para definir um diagrama. Resultados: Foram encontrados diferentes tamanhos de arcadas dentárias linguais, tanto para a maxila quanto para a mandíbula. Os menores tamanhos foram os femininos, e os maiores, os masculinos. Definiram-se seis tamanhos para cada sexo, sendo três para a maxila e três para a mandíbula, nomeados como P, M e G. Foi criado um diagrama com dezoito desenhos de arcos linguais anatômicos, nove para a maxila e nove para a mandíbula, para ambos os sexos. Conclusões: A posição dos pontos de referência nesse estudo evidenciou diferenças entre os sexos, o que permitiu a criação de arcos mais compatíveis com as formas e dimensões anatômicas da maxila e mandíbula. A diferença entre os tamanhos das arcadas dentárias linguais possibilitou a criação de um diagrama com formas de arcos metálicos linguais anatômicos para serem utilizados na técnica lingual, para auxiliar o profissional a criar os seus próprios arcos.